Vegetative material age and its effect on rooting shoots of coffea (coofea arabica) variety caturra - Vásquez Inuma, Lady Liliana (2018)
The present investigation was carried out in the facilities of the Clonal Coffee Biotechnology greenhouse of the Peruvian Amazon Research Institute, San Martin-Peru headquarters. The objective was to determine the appropriate age of harvest of the coffee shoots (Coffea arabica L.) for its optimum rooting under controlled conditions. Coffee shoots were tested with ages between 55-64 and 65-74 days. The shoots were subjected to a previous disinfection and exposed to a dose of hormone indole-3-butyric acid (IBA) of 1000 ppm, then placed in jiffy pellets and finally introduced in microtuneles with controlled conditions to encourage rooting. For the analysis a completely randomized factorial experimental design was used, whose factors correspond to age of the shoots, hormonal treatment (AIB) and 6 repetitions, with 24 experimental units in total, the latter being comprised by 6 coffee shoots, making a total of 144 shoots. After six weeks of the trial, the outbreaks were evaluated, for the variables: root number, root length, rooting percentage and mortality. The data were systematized and subjected to an analysis of variance and a Tukey test. Concluding that the recommended age of the coffee shoots to obtain plants with optimum rooting is in the range of 65 to 74 days.